Organic Phosphorus in the Environment 2004
DOI: 10.1079/9780851998220.0089
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic hydrolysis of organic phosphorus.

Abstract: This paper discusses the enzymatic hydrolysis of organic phosphorus with reference to the classical inorganic and organic compartmental analysis of phosphorus compounds in ecosystems. Also discussed are: the potential use of soil organic phosphorus by plants and microorganisms; properties of phosphohydrolases; inhibitors and activators; phosphohydrolase activity in soil; rhizosphere and mycorrhizal aspects of phosphohydrolase activity; and the regulation of the phosphohydrolase activity in the rhizosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 0 publications
0
63
1
3
Order By: Relevance
“…Inositol phosphates, phospholipids and nucleic acids are the dominant forms of organic phosphorylated compounds in soils (Quiquampoix and Mousain 2005) and inositol phosphates have been reported to be the main form of organic phosphorus (Po) in soil (Dalal, 1977). Because actinomycetes are widely distributed in different soil ecosystems, it has been assumed that they are capable of hydrolyzing phytate (myo-inositol (1,2,3,4,5,6) hexakisphosphate).…”
Section: Soil Characteristics and Actinomycetes Populationmentioning
confidence: 99%
“…Inositol phosphates, phospholipids and nucleic acids are the dominant forms of organic phosphorylated compounds in soils (Quiquampoix and Mousain 2005) and inositol phosphates have been reported to be the main form of organic phosphorus (Po) in soil (Dalal, 1977). Because actinomycetes are widely distributed in different soil ecosystems, it has been assumed that they are capable of hydrolyzing phytate (myo-inositol (1,2,3,4,5,6) hexakisphosphate).…”
Section: Soil Characteristics and Actinomycetes Populationmentioning
confidence: 99%
“…A recent study revealed that two fungal phytases are rapidly absorbed to the soil solid phase, their physicochemical properties affecting their mobility, temporal stability and capacity to hydrolyze inositol phosphate in soil 24) . Absorption of microbial phytases may also reduce their affinity for inositol phosphate and thus reduce their effective activity 84) . Moreover, the effectiveness of phytases in increasing the availability of P to plants may be further limited by the concentration of organic P forms in the soil solution 22) .…”
Section: Phytate-producing Bacteria As Plant Growth-promoting Agentsmentioning
confidence: 99%
“…The enzyme N-acetyl b-glucosaminidase is mostly present in soils in extracellular forms (Parham and Deng 2000) and can be produced by microorganisms in response to N-deficiency to acquire N from organic matter (Sinsabaugh and Moorhead 1994;Olander and Vitousek 2000;Muruganandama et al 2009). Phosphomonoesterase is released by microorganisms in response to phosphorus (P) deficiency to hydrolyze ester bonds between C and P in organic matter and liberate orthophosphate (Quiquampoix and Mousain 2005). Activity of these enzymes can indicate microbial mineralization of nutrients from organic matter due to N or P demand (Olander and Vitousek 2000;Allison et al 2007;Sinsabaugh et al 2008) and consequently may provide a useful indication of nutrient limitation during priming.…”
Section: Introductionmentioning
confidence: 99%